Chemical characterization and solvent fractionation of tilapia oil for its potential application as human milk fat substitute. Issue 11 (6th October 2022) - Cheng, Xinyi; Huang, Zhuoneng; Jin, Qingzhe; Wang, Xiaosan
Abstract : Abstract: The natural source of human milk fat substitute (HMFS) is a field worth exploring. In this study, tilapia oil was extracted and analyzed. In the triacylglycerol fraction, the contents of sn ‐2 palmitic acid and total sn ‐1, 3 oleic acid and linoleic acid were 48.01% and 66.62%, respectively. The optimal solvent fractionation conditions were determined to be a tilapia oil‐to‐acetone ratio of 1:8 (w/v), crystallization temperature of −30°C, and crystallization duration of 16 h, giving a solid fraction yield of 64.20%. In fractionated tilapia oil, the total content of 1‐oleoyl‐2‐palmitoyl‐3‐linoleoylglycerol (OPL) and 1, 3‐dioleoyl‐2‐palmitoylglycerol (OPO) increased by 20.38%, as determined by reversed‐phase liquid chromatography. Ultra‐high‐performance combined‐phase chromatography combined with quadrupole time‐of‐flight mass spectrometry analysis showed that OPL (17.45%) was the most abundant triacylglycerol in fractionated tilapia oil, followed by OPO (13.90%). Fractionated tilapia oil is thus an excellent source of OPL and has great potential for incorporation in HMFS. Practical Application: Human milk fat substitutes are an important component of infant formulas. This work provides an excellent natural source of oil rich in OPL, which has great potential in the field of preparing human milk fat substitutes highly similar to human milk fat.